ANALISIS KUALITAS PERAIRAN SELAT RUPAT SEKITAR AKTIVITAS INDUSTRI MINYAK BUMI KOTA DUMAI - Yeeri Badrun (Jurnal Ilmu Lingkungan, 2008)
The study was conducted from November 2006 to May 2007 at around activities of crude oil industry in Dumai.The purpose of this research is to determinate the pollution rates at water level surface based on physic-chemistry parameters, and the correlations of pollution rates to macrozoobenthos in basin. The method of studyconsisted of several step from determination of sampling station for 8 stations; measurement of Pollutant Index(IP) based on water physic-chemistry parameters; whereas Pollutant Degree (DP) based on macrozoobenthosdiversity. The analysis of clusters was used to classify pollution rates based on stations distribution. Spearmancorrelation test was used to get the correlation between IP and DP. During 2002 to 2006, IP value averages atstudy locations between 0,17 – 0,93 was classified in unpolluted with tendency in good relatively. Whereas DPvalue averages between 2,40 – 2,67 was classified in moderate polluted with tendency in good relatively.